FAKTOR DETERMINAN INDEKS PEMBANGUNAN MANUSIA DI PULAU JAWA - Devitama Patria Nagara; Masruri Muchtar; Pardomuan Robinson Sihombing (LPPM Universitas Bina Bangsa, 2024)
This study aims to analyze the effect of home ownership rate, proportion of labor, and crime settlement rate on Human Development Index (HDI) in 6 provinces in Java Island in the period 2015 to 2019. This study used regression panel data sourced from the Central Statistics Agency. The results of this study show that households with their own home ownership have an effect on HDI but the proportion of formal labor and crime resolution rates do not have a significant impact. This finding has implications for regional development policies in Java. Households with self-owned home ownership play an important role in improving the Human Development Index (HDI) by creating stability and security of individual residences. However, the proportion of the formal workforce and the rate of solving crimes do not have a significant impact on HDI, demonstrating the complexity of the factors affecting human development. The implications of these findings can be used as a basis for designing more targeted policies to improve people's welfare at the regional level. Factors such as home ownership can be considered as the main focus in efforts to improve the quality of life and human development in Java